Electron energy distribution function in the divertor region of the COMPASS tokamak. (March 2016) - Dimitrova, M; Hasan, E; Ivanova, P; Vasileva, E; Popov, Tsv; Dejarnac, R; Stöckel, J; Panek, R
Abstract: The plasma parameters during an L-mode hydrogen discharge in the COMPASS tokamak with a toroidal magnetic field BT =1.15 T, line-averaged electron density ne = 6×10 19 m -3 and a plasma current variation from 209 kA to 100 kA were studied in the divertor region. The electron energy distribution function for 209 kA at the high-field side and the private region is Maxwellian with a temperature in the range of 5 – 9 eV, while around the outer strike point and the low-field side it is bi-Maxwellian with a low-energy electron group (4 – 5 eV) and higher energy electrons (10 – 20 eV). As the plasma current decreases, the appearance of the bi-Maxwellian EEDF is shifted towards the low-field side; at plasma current of 100 kA, the EEDF is Maxwellian in the whole divertor region.